2016
DOI: 10.1016/j.exger.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Absence of premature senescence in Werner's syndrome keratinocytes

Abstract: Werner's syndrome (WS) is an autosomal recessive genetic disorder caused by loss of function mutation in wrn and is a useful model of premature in vivo ageing. Cellular senescence is a plausible causal mechanism of mammalian ageing and, at the cellular level, WS fibroblasts show premature senescence resulting from a combination of telomeric attrition and replication fork stalling. Over 90% of WS fibroblast cultures achieve less than 20 population doublings (PD) in vitro compared to wild type human fibroblast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The mesenchymal lineage and connective tissue (e.g., fibroblasts) are overall more severely affected, which might be attributed to the premature senescence phenotype. However, premature senescence in vivo has been challenged by recent findings using dermal fibroblasts from autopsied WS patients (Ibrahim et al, ; Tokita et al, ). From our study, although premature senescence of WS‐MSCs (compared with gene‐corrected MSCs) could be observed in late passages, HGF deficiency was observed when MSCs were immediately differentiated from mesoderm precursors.…”
Section: Discussionmentioning
confidence: 99%
“…The mesenchymal lineage and connective tissue (e.g., fibroblasts) are overall more severely affected, which might be attributed to the premature senescence phenotype. However, premature senescence in vivo has been challenged by recent findings using dermal fibroblasts from autopsied WS patients (Ibrahim et al, ; Tokita et al, ). From our study, although premature senescence of WS‐MSCs (compared with gene‐corrected MSCs) could be observed in late passages, HGF deficiency was observed when MSCs were immediately differentiated from mesoderm precursors.…”
Section: Discussionmentioning
confidence: 99%
“…As another example, keratinocytes, which comprise the epidermal tissue of the skin, have been reported to evade premature telomere dysfunction caused by WRN helicase deficiency [ 79 ]. Unlike fibroblasts in the dermis, keratinocytes possess telomerase activity and thereby play an important role in skin regeneration [ 80 ].…”
Section: Pathophysiological Research Using Pluripotent Stem Cellsmentioning
confidence: 99%
“…Other studies have suggested that epidermal stem cell function is retained throughout life, as the abundance and functional capacity of epidermal stem cells were similar between young and aged murine skin, with regard to telomere length and expression of senescent markers (Giangreco et al, 2008 ; Stern & Bickenbach, 2007 ). Similarly, keratinocytes derived from Werner syndrome patients do not show evidence of premature senescence when cultured in vitro (Ibrahim et al, 2016 ).…”
Section: Molecular Mechanisms Of Skin Ageingmentioning
confidence: 99%